Analysis of Problem Formulation Skill of High School Students - Erawarni, Dian; Wiyanto, Wiyanto; Yulianti, Ian (Physics Communication, 2021)
This study aims to analyze the pattern of problem formulation skills and hypothesize students of class XI MIPA at SMAN 2 Grabag and SMA Islam Sudirman Pakis. The research design is qualitative research. The technique used in the data collection was an interview technique with 20 students and two physics teachers, as well as documentation during the research. Before the interview, the students observed 3 physical phenomena, namely (1) phenomenon 1 regarding the effect of oxygen on the flame of a candle, (2) phenomenon 2 regarding water surface pressure on razor blades and needles, (3) phenomenon 3 regarding eggs that put in various solutions with different density. The data analysis technique was qualitative analysis. Based on the research, all students were able to formulate problems according to the video of the observed phenomena, and based on the problem formulation proposed by the students found that there are three patterns of problem formulation in phenomenon 1, two patterns of problem formulation in phenomenon 2, and three patterns of problem formulation in phenomenon 3, with all problem formulation patterns proposed by students being problem formulations that correspond to each previously observed phenomenon. This shows that all students have good problem formulation skills, it can be seen that students can identify problems in each video phenomenon and ask them in the form of questions. The results showed 2 question words, those are "why" as much as 77% and the question word "what" as much as 23%. Students who formulate problems using the question word "why" can be categorized at the formal operational stage and students who formulate problems using the question word "what" can be categorized at the concrete operational stage. This difference in students' cognitive development can be a guide for teachers to use a student-focused learning model.